In Memoriam the mathematicians of Vilnius University - Jasiūnas, Henrikas; Verikaitė, Vitolda (Lietuvos matematikos rinkinys, 2004)
Mathematcians of old Vilnius University, whose tombs are known to us, have been mentioned in this paper. Those mathematicians deceased more recently, as well as contemporary ones, are honored for their contributions to the mathematical sciences in hopes of nurturing a younger generation of mathematicians.
Keywords: University,; faculty; professor; associate professor; mathematician; cemetery